The influence of Diversity, Inclusion, and People Development (DIP) on ESG performance in conventional banking - Shooma Fikri Albaasith; Nurika Restuningdiah; Triadi Agung Sudarto (Greenation Research & Yayasan Global Resarch National, 2025)
This study aims to analyze the influence of Diversity, Inclusion, and People Development (DIP) on Environmental, Social, and Governance (ESG) performance in the conventional banking sector in Indonesia during the 2021–2023 period. Based on Stakeholder Theory, this study argues that a bank's success is not only measured by profitability, but also by its ability to accommodate the interests of employees and communities through robust DIP practices. Using an explanatory quantitative method with a purposive sampling technique, this study involved 24 conventional banks listed on the Indonesia Stock Exchange, resulting in a total of 72 observation units analyzed using multiple linear regression. The results of the hypothesis testing indicate that the Diversity and People Development variables have a positive and significant influence on ESG performance, confirming that diverse perspectives and investment in human capital development are key pillars in strengthening corporate sustainability. Conversely, the Inclusion variable was found to have a negative and significant influence on ESG performance, indicating strategic inefficiency where current inclusion policies are still considered an operational burden that increases costs without providing direct returns on ESG scores. This study concludes that although HR development has become a mature industry standard, banks need to re-evaluate the effectiveness of the implementation of inclusion policies so that they can create sustainable strategic value and not just become an administrative formality.